Trading conflicts - Christ, Georg.
1 online resource (384 pages)
Keywords: Analysing different conflicts in Late Medieval Alexandria, this book offers new insights into the micro-mechanics of Venetian life and trade in Egypt and recalibrates the narrative of the strictly regulated and often violent contacts between East and West. This thorough microanalysis, based on the private archive of a Venetian merchant and consul in Alexandria read in conjunction with other Venetian and Mamluk sources, provides a differentiated image of conflict patterns cutting across the cultural divide. It transforms our image of Alexandria as a city at the intersection of Orient and Occident into that of a microcosm in its own right where disputes did not always fall neatly along cultural divides and conflicts were traded as much as trade created conflicts.